Sistemas Públicos de Educação Básica e Relações Intergovernamentais: a ação da União e a autonomia dos sistemas locais de ensino - Duarte, Marisa Ribeiro Teixeira (2003)
The fundamental question addressed in this study is related to the implementation of the colaborative hierarchy, established by the Federal Constitution of 1988 (caput, art 211). The objective deals with the apprehension of the concrete mechanisms of its implementation. The political-judicial autonomy established for the local elementary educational system established is analysed in view of the restrictions imposed by the higher levels of government. What is the type of autonomy of the system constructed after 1996? This analysis highlights the political nature of the relations between the educational systems with the goal to expand the coverage of basic elementary education, which, in turn would provide better access and equalize opportunities for all. The analysis of the relations between the public financing network and the capacity of local government agencies to implement educational policies has been prioritized in this study.